2011
DOI: 10.1089/ars.2010.3555
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Alpha7 Nicotinic Acetylcholine Receptor by Nicotine Attenuates Inflammatory Response in Macrophages and Improves Survival in Experimental Model of Sepsis Through Heme Oxygenase-1 Induction

Abstract: Activation of nicotinic acetylcholine receptor alpha7 subunit (α7nAChR) by nicotine leads to the improved survival rate in experimental model of sepsis. Previously, we demonstrated that heme oxygenase (HO)-1 inducers or carbon monoxide significantly increased survival of lipopolysaccharide (LPS)-induced and cecal ligation and puncture-induced septic mice by reduction of high mobility group box 1 release, a late mediator of sepsis. However, that activation of α7nAChR by nicotine provides anti-inflammatory actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 49 publications
(64 reference statements)
7
56
0
Order By: Relevance
“…It has been already documented that the HO-1/CO system provides a therapeutic effect in many experimental pathological conditions (2,31). Recently, we and others demonstrated that HO-1/CO can improve survival and decrease the circulating HMGB1 level in septic animals, which further supports beneficial effects of HO-1 in inflammatory disorders (37,38,40).…”
supporting
confidence: 65%
See 2 more Smart Citations
“…It has been already documented that the HO-1/CO system provides a therapeutic effect in many experimental pathological conditions (2,31). Recently, we and others demonstrated that HO-1/CO can improve survival and decrease the circulating HMGB1 level in septic animals, which further supports beneficial effects of HO-1 in inflammatory disorders (37,38,40).…”
supporting
confidence: 65%
“…Under the Nrf2 activation, it dissociates from Kelch-like ECHassociated protein 1 (Keap1) and translocates into the nucleus, where it binds ARE (18). Different pathways may activate Nrf2, including PI3K/Akt and MAPKs (6,13,38). We found that EP can activate Nrf2 by enhancing Nrf2 nuclear accumulation and the ARE-luciferase activity.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, the ELISA results complemented the RT-PCR array findings and vice versa. These results also indicate that transcriptional activation or repression of IL-6 and TNF-a (among others) following poly(I:C) stimulation or poly(I:C) 1 nicotine treatment accompanied an increase or decrease, respectively, in proinflammatory cytokines: an indication that gene activation or repression is involved in their actions, although other mechanisms (Tsoyi et al, 2011) could also be active. Similarly, antibody array results complement Western blotting findings and vice versa: CamKIIa phosphorylation was reduced in nicotine 1 poly(I:C)-treated cells in both assays.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, CO regulates monocyte/ macrophage activation (42), an effect associated with protection against different experimental models of disease (43,51). Induction of HO-1 expression by different nicotinic receptor agonists and its importance in the maintenance of antiinflammatory effects have been recently reported (57). On the other hand, induction of GCL-c, the rate-limiting enzyme of the novo synthesis of glutathione (GSH), by melatonin increases the levels of GSH and protects against oxidative stress (58).…”
Section: Innovationmentioning
confidence: 99%